Window-type rupture of carbon steel pipe in a hydroprocessing plant of a petroleum refinery due to ammonium bisulfide corrosion. (February 2021) - Al-Mazeedi, H.A.; Al-Wakaa, B.; Ravindranath, K.
Highlights: An investigation was carried out to identify the root cause of the failure of carbon steel piping. The pipe suffered localized thinning and rupture. The accelerated corrosion resulted hydrogen induced cracks in the pipe. The failure of the pipe was due to erosion corrosion contributed by ammonium bisulfide. Abstract: The window-type rupture of a carbon steel piping in a refinery hydrocracking plant was investigated to identify the root cause of failure. The comprehensive investigation included visual examination, optical and scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and hardness measurements. The results of the investigation indicated that the failure of the piping was as a result of an aggressive corrosion reaction contributed by ammonium bisulfide (ABS) and turbulence. An increase in the throughput, change in the feed quality and localized turbulence due to geometry synergized the corrosion reaction. The aggressive conditions that existed in the system led to accelerated erosion corrosion. The accelerated erosion-corrosion resulted in the thinning of the pipe at the location and finally in the brittle window rupture of the pipe. The aggressive corrosion reaction also resulted in the generation of atomic hydrogen, which entered into the steel and caused hydrogen-induced cracking (HIC) at the thinned locations. Recommendations made to avoid reoccurrence of the incidence of corrosion and failure included reducing the severity of corrosive conditions and up-gradation of the material of construction to Alloy 825.